Pelembagaan Prinsip Dasar Demokrasi dalam Legislasi Peraturan Daerah di Jawa Timur - Anis Ibrahim (Fakultas Hukum Universitas Islam Indonesia, 2012)
This research aims at disclosing empirically legislation practices of regional regulations (Perda) which are analyzed based on the basic principles of democracy. The problems in this research are formulated as follows: (1) Why does the legislation of Regional Regulations in East Java tend to be conducted in elitist way? (2) What factors do obstruct the institutionalization of the basic principles of democracy in the legislation of Regional Regulations in East Java? And, (3) How is the future conceptualization of legislation of Regional Regulations in democracy perspective? To answer the questions, this research uses socio-legal research approach. The result of the research shows that: first, (a) there is a reluctance of the regional elites to disseminate and give room to the community to continually participate in the legislation of Regional Regulations, (b) the process is time-consuming and circuitous, (c) the discussion in Raperda (Regional Regulations meeting) is not focused, (d) lack of budget for the legislation of Regional Regulations activities, (e) not all people understand the matters regulated in Raperda, and (f) regional elites consider that Raperda has already been discussed thoroughly between DPRD (Regional House of Representative) and Regional Government. Second, there are 5 (five) factors that impede the institutionalization of basic principles of democracy in the research area, namely: (a) legal substantial factor,(b) legal structural factor, (c) legal cultural factor, (d) time factor, and (e) budget factor. Third, elite expectation must meet and be harmonious with public expectation.